The analysis of Eric von Rosen’s archaeological collection (Etnografiska museet, Sweden): the contribution of the Swedish Chaco-Cordillera Expedition to the study of mining and metallurgy in the Puna of Jujuy, Argentina - María Florencia Becerra (Journal de la Société des Américanistes)
This paper approaches the Swedish Chaco-Cordillera Expedition to the North of Argentina and South of Bolivia (1901-1902) and it focuses on the archaeological objects recovered. Besides the analysis performed by Eric von Rosen in 1902-1903, no further in-depth studies of the collection had been since carried out, despite its great potential to elucidate different aspects of the Andean and lowlands’ pre-Columbian past. Combining the analysis of the publications made by the members of the expedition and their unpublished personal documentation, as well as the study of the collection itself, this paper aims to offer new data on these findings and show the contribution that these materials, and the interpretations the Swedish researchers formulated about them, made to the understanding of the metallurgy and mining activities developed during the pre-Columbian Late Period (AD 1200-1550) in the Puna of Jujuy, Argentina.